Constraints in Production of Orange (Citrus reticulata Blanco) in Vidharbha Region of Maharashtra (Indian Journal of Extension Education, 2012)
The present study was conducted in Vidharbha region of Maharashtra with specific objectives to study the constraints faced by orange (Citrus reticulata Blanco) growers in cultivation and marketing and to provide suggestions offered by growers to overcome these constraints. Three districts, namely Nagpur, Amaravati and Wardha, purposively selected and from each district two blocks and from each block two villages were randomly selected. Ten farmers from each village were selected randomly to make 120 samples. The major constraints were high incidence of disease, frequent shedding of electricity, lack of disease resistant varieties and lack of information regarding improved orange variety. High fluctuation of price, price not according to quality of produce, lack of cold-storage facilities and more commission charged by commission agents. The important suggestion offered by growers were: establishment of cold storage facilities at village level, easy accessibility of credit with low interest rate and timely electricity supply with low cost, establishment of processing industries at production-catchments area, establishment of co-operative marketing agencies, government support during crop failure and lower down the commission charged by APMCs.